The Influence of Different Interstock Lengths of Minneola Tanjelo on Photosynthetic Parameters and Fruit Yield of Star Ruby Grapefruit - Bilge Yılmaz; Berken Çimen; Müge Uysal Kamiloğlu; Meral İncesu; Turgut Yeşiloğlu; Muharrem Yılmaz (Turkish Journal of Agriculture: Food Science and Technology)
In this study, Minneola Tangelo hybrid, a cross of grapefruit and mandarin (Duncan grapefruit x Dancy mandarin), used as interstock to Star Ruby grapefruit with different lengths. Effects of different interstock lengths on fruit yield and quality, plant development and photosynthetic parameters were investigated. According to the results, different interstock lengths significantly affected fruit yield and size. The highest fruit yield was determined in T-M20-S whereas the lowest was on T-M5-S. The highest fruit size were determined in Star Ruby fruits on T-M5-S and T-M40-S whereas the lowest on T-M20-S and T-S (control). T-M40-S and T-M20-S treatments markedly reduced stem diameter and tree canopy in comparison to other treatments and control. Usage of different interstock lengths did not significantly affected some of fruit quality traits, net photosynthetic rate, stomatal conductance, leaf transpiration rate, leaf water usage efficiency and leaf chlorophyll concentration. In regards to seasonal changes, net photosynthetic rate were higher in spring and summer seasons then winter and fall seasons.